Tuning the phase transition temperature of ferronematics with a magnetic field. Issue 9 (13th February 2018) - Tóth-Katona, Tibor; Gdovinová, Veronika; Tomašovičová, Natália; Éber, Nándor; Fodor-Csorba, Katalin; Juríková, Alena; Závišová, Vlasta; Timko, Milan; Chaud, Xavier; Kopčanský, Peter
Abstract : Magnetic field-induced phase transition temperature shifts detected in liquid crystals (LCs), their mixtures, and ferronematics (FNs) based on them. Abstract : The influence of magnetic field on the isotropic-to-nematic phase transition temperature is investigated in neat bent-core and calamitic liquid crystals, in their mixture, and in samples doped with spherical magnetic nanoparticles for two different orientations of the magnetic field. A magnetic-field-induced negative or positive shift of the transition temperature was detected depending on the magnetic field orientation with respect to the initial orientation of the nematic phase, and on the type of liquid crystal matrix.